(untitled) (Confluenţe Bibliologice, 2017)
The AGORA database on the Research4Life platform provides access in the field of agriculture, ecology, medicine, environmental sciences and social sciences. The librarian of the Scientific Library and the USARB young researchers participated in the Workshop "Access to agricultural online information"held in Chisinau between 27-28 November 2017.